USE THE QUEUE THEORY TO ASSESS THE QUALITY STANDARDS OF SERVICE SYSTEMS TO ACHIEVE THE CUSTOMER'S DESIRE - Ass. Lecturer Ali Fakhri Abbas; Dr. Ahmed Amer Najaf (Scholar Express Journals, 2024)
Control of the impact of quality on the performance of organizations is one of the most important things in today's business environment. For growth and development, quality and achieving customer satisfaction have become an obsession for service institutions as customer satisfaction has become the main focus of their interests, so this approach is considered one of its primary goals that must be achieved, which is necessary It must pool its efforts towards achieving these goals, in order to provide a quality service that meets the needs of customers and achieves their satisfaction. The issue of measuring the quality of service systems is seen through the specific dimensions of that, which depend on the method of accountability in some of them, such as the behavior of employees in these service centers, as well as the quantitative method in others as the length of service and waiting. The latter adopts dynamic models in which the element of time plays an important role, especially in queue models. The most important finding of the study is that increasing the shop’s employees also leads to reducing the total costs of the shop from losing customers who cannot find a place to wait, but through careful studies that do not lead to increasing the total costs
Keywords: Queuing theory; Quality of service; Service quality standards